Glucose Supply Control Using Silver Meal Heuristic Method at PT. XM Sidoarjo - Titik Koesdijati; Djoko Adi Waluyo (UNIPA PRESS, 2022)
Abstract Inefficient supply of glucose is a problem for PT XM Sidoarjo, where too much raw material inventory can result in high storage costs, or too little inventory causes the production process to stop. The research uses the Silver Meal Heuristic method which is based on future demand, so that the purchase of raw materials can be determined precisely. The company calculates the cost of raw materials and storage for a year using the Company's Real Method is around Rp. 16,465,582,200. If using the Heuristic Silver Meal method, the number of orders for glucose by predicting the optimal number of orders for raw materials to meet the inventory needs every month is 1,050.62 tons at a cost of Rp. 1,261,094,000. so the total cost from January to December 2020 will be Rp 15,133,128,000. Thus the savings that can be made from January to December 2020 is Rp. 1,332,454,200 with an efficiency of 8.09%. Keywords: Inventory Control, Silver Meal Heuristic Method, Glucose Raw Material.